2018
DOI: 10.1200/jco.2017.74.8491
|View full text |Cite
|
Sign up to set email alerts
|

Web-Based Stress Management for Newly Diagnosed Patients With Cancer (STREAM): A Randomized, Wait-List Controlled Intervention Study

Abstract: PurposeBeing diagnosed with cancer causes major psychological distress; however, a majority of patients lack psychological support during this critical period. Internet interventions help patients overcome many barriers to seeking face-to-face support and may thus close this gap. We assessed feasibility and efficacy of Web-based stress management (STREAM [Stress-Aktiv-Mindern]) for newly diagnosed patients with cancer.Patients and MethodsIn a randomized controlled trial, patients with cancer who had started fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
130
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(134 citation statements)
references
References 38 publications
1
130
2
1
Order By: Relevance
“…Cancerspecific distress did not significantly moderate outcomes at any time point. Table 3 These outcomes add to the findings from three recent RCTs of online programs for recently diagnosed acute cancer survivors [19,15,18]. In contrast with the CancerCope trial for newly diagnosed distressed-patients [19], where no QOL impact was found, our study found FMW significantly improved emotional functioning.…”
Section: No Significant Differences Between Groups Were Observed For supporting
confidence: 69%
See 2 more Smart Citations
“…Cancerspecific distress did not significantly moderate outcomes at any time point. Table 3 These outcomes add to the findings from three recent RCTs of online programs for recently diagnosed acute cancer survivors [19,15,18]. In contrast with the CancerCope trial for newly diagnosed distressed-patients [19], where no QOL impact was found, our study found FMW significantly improved emotional functioning.…”
Section: No Significant Differences Between Groups Were Observed For supporting
confidence: 69%
“…Phase I and II trials demonstrated feasibility and pilot efficacy of the first iteration of this unguided program, Cancer Coping Online, in improving distress, maladaptive coping, and select quality of life domains [14,15]. Two further RCTs have recently been published; a German study comparing the therapist-guided CBT and mindfulness program "STREAM" against a waitlist control in 129 patients [18]; and an Australian study of an unguided web-based CBT program 'CancerCope' for 163 patients screened with high distress, compared to a static cancer education website [19]. The STREAM program led to improved quality of life and reduced distress, but no impact on anxiety or depression [18].…”
Section: Word Count: 248mentioning
confidence: 99%
See 1 more Smart Citation
“…It can be considered as an advantage of this study that the educational effect was persistent after three months of intervention. In other studies that have examined the impact of Web-based or Internet-based interventions on QoL of cancer survivors, social performance has not changed significantly after interventions [41][42][43]. Although these methods and social network-based methods are not ineffective and they have a high rate of patient participation due to their ease of access, one of their biggest challenges is low treatment adherence, which affects treatment effectiveness [19].…”
Section: Meanwhile Compen Et Al Compared the Effect Of Routine Treamentioning
confidence: 99%
“…Weiterhin wurden Ergebnisse über zu geringe Fallzahlen, ungenaue primäre Outcomes sowie fehlende Kontrollgruppen berichtet, sodass es momentan schwierig ist, eindeutige Aussagen über Effektivität von eHealth Interventionen in der Psychoonkologie zu treffen [20]. Die neueren eHealth Studien STREAM [21] und BREATH [22] die im RCT Design durchgeführt worden sind zeigen, dass eHealth Interventionen im Umgang mit psychoonkologischen Belastungen und bei der Krankheitsverarbeitung hilfreich sind und einen klaren klinischen Benefit für die Patientinnen zeigen. In den verschiedenen Studien wird allerdings klar formuliert, dass es einen großen Bedarf an weiterer Forschung und RCT Studien gibt, um webbasierte Interventionen der Evidenz folgend zu verbessern und um eindeutige Schlussfolgerungen über die Wirksamkeit von eHealth Interventionen machen zu können [23][24][25][26][27].…”
Section: Introductionunclassified